Process mapping and management - Conger, Sue A. ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2011)
As the economy moves toward a services orientation, companies are struggling with how to improve their offerings. Process management is a key component of the services that companies provide. This book has three main parts: mapping, improvement, and error-proofing and metrics. In the first part--mapping--the reader will learn how to map a process so that the map is immediately understandable for identifying the roles, work steps, and automation support used in process delivery. The second part--improvement--provides a series of techniques for defining, prioritizing, and analyzing problems from several perspectives. The first perspective is called'leaning,' and its purpose is to remove waste from an existing process. The second perspective is'cleaning,' during which the remaining steps following leaning are analyzed for possible improvement. The third perspective is'greening,' which explores opportunities and trade-offs for outsourcing, coproduction, and environmental improvements related to the process. The final third of the book--error-proofing and metrics--presents several techniques for ensuring risk mitigation for the new process and for measuring changes that define their impacts, and illustrates a method for proposing changes to executives in a'case for change.' Overall, the book provides a blueprint of how to develop a discipline for process management that applies to any type of work.
List of figures -- Part I. Opening gambit -- 1. Introduction -- 2. Process improvement project initiation -- 3. Process mapping I -- 4. Process mapping II -- Part II. The middle game -- 5. Problem finding -- 6. Process leaning -- 7. Process cleaning -- 8. Process greening -- Part III. End game -- 9. Process redesign -- 10. Measures and final report -- Appendix A. Final report for the SCI Call Center: technology analysis -- Appendix B. Additional reference materials -- Notes -- References -- Index.
Includes bibliographical references (p. 429-448) and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Keywords: Production planning; Process control; Management; Process; Improvement; Statement of work; Value-added analysis; Root-cause analysis; Six Sigma; Quality function deployment; Statistical process control; Failure-proofing.; Metrics; Case for change